Assessment of evapotranspiration loss of water from rice and wheat plants grown in sand and sandy soil in earthen pots under flood irrigation (Dhaka University Journal of Biological Sciences, 2018)
Abstract not availableDhaka Univ. J. Biol. Sci. 27(2): 221-224, 2018 (July)